Hepatocellular carcinoma is diagnosed at a later stage in alcoholic patients: Results of a prospective, nationwide study. Issue 9 (28th March 2018) - Costentin, Charlotte E.; Mourad, Abbas; Lahmek, Pierre; Causse, Xavier; Pariente, Alexandre; Hagège, Hervé; Dobrin, Anca Stela; Becker, Claire; Marks, Bérangère; Bader, Robert; Condat, Bertrand; Héluwaert, Frédéric; et al.
Abstract : BACKGROUND: Recent data suggest that alcohol‐related hepatocellular carcinoma (HCC) is diagnosed at a later stage. The aim of this study was to compare HCC characteristics and outcomes in an alcohol‐related group (group A) and a non–alcohol‐related group (group NA). METHODS: A total of 1207 patients with newly diagnosed HCC were prospectively included between May 2008 and October 2009. Patients with multiple causes (alcohol plus another cause) were excluded. Patients were followed every year for 5 years. Recorded variables, including etiologies were tested as prognostic factors of survival in a multivariate Cox model after adjustments for a lead‐time bias. RESULTS: In all, 894 patients were analyzed: 582 (65.1%) were in group A, and 312 (34.9%) were in group NA. Alcohol‐related HCC was more likely to be diffuse and detected in patients with a worse performance status and worse liver function. After adjustments for a lead‐time bias, the median overall survival (OS) was 9.7 and 5.7 months in groups NA and A, respectively ( P = .0002), and 5.8 and 5.0 months in alcohol‐abstinent and alcohol non‐abstinent groups, respectively ( P = .09). The prognostic role of alcohol disappeared when survival was assessed at each Barcelona Clinic Liver Cancer (BCLC) stage. Patients with HCC detected during a cirrhosis follow‐up program (n = 199 [22.3% of the whole cohort]) had increased lead time–adjusted median OS in comparison with patients with HCC diagnosed incidentally (11.7 vs 5.4 months; P < .0001). CONCLUSIONS: In comparison with patients with non–alcohol‐related HCC, patients with alcohol‐related HCC have reduced OS, mainly because of worse liver function and tumor characteristics at diagnosis, as attested by similar survival within each BCLC stage. Cancer 2018;124:1964‐72 . © 2018 American Cancer Society . Abstract : In comparison with patients with hepatocellular carcinoma not related to alcohol, patients with alcohol‐related hepatocellular carcinoma have reduced survival. Patients with hepatocellular carcinoma detected during a cirrhosis follow‐up program have increased survival in comparison with patients with hepatocellular carcinoma diagnosed incidentally.